A Collaborative Approach to Paraeducator Training. (April 2021) - Douglas, Sarah N.; Uitto, Denise J.
Many schools struggle to provide appropriate training for paraeducators to ensure the necessary knowledge and skills required to support students with challenging behaviors. This article provides a collaborative approach to paraeducator training. Included is a description of a four-step strategy to clarify paraeducator responsibilities and define training needs, create training plans that align with adult learning principles, implement training using coaching with performance feedback, and document paraeducator performance. Roles for team members and examples for training are provided.